KAJIAN STRATEGIS PENGEMBANGAN EKONOMI WILAYAH PESISIR KECAMATAN TANJUNG PALAS TIMUR - Arifin, Asfihannur; Roem, Muhamad (Jurnal Harpodon Borneo, 2016)
The perception of the coastal regions that identic with poor fishermens, low level of the economy, uneducated and unhealthy environment was as a raw portrait. It also found on coastal area of Tanjung Palas Timur District of Bulungan. There are factors causing low accessibility of people to markets and capital as well as the informal system formed trading marine fishermen bargaining position unfavorable. This study is intended to find a formulation of draft strategies, programs and action plans in order to facilitate the potential and prospects in the region of the study. The results of this study include potential into capital as a force to be developed as well as the prospects of the existing opportunities to be handled appropriately, provide alternative overcome weaknesses in order to cope with market competition outside of the study area.Key words : coastal area, economic district, strategic of study